ChemInform Abstract: Synthesis of Polysubstituted Benzenes from 2‐Pyrone‐4, 6‐dicarboxylic Acid. Issue 13 (March 2015) - Okura, Keisho; Tamura, Ryuichi; Shigehara, Kiyotaka; Masai, Eiji; Nakamura, Masaya; Otsuka, Yuichiro; Katayama, Yoshihiro; Nakao, Yoshiaki
Abstract The thermal decarboxylative cycloaddition of the title compound and its dimethyl ester with vinyl acetates (I) and (IV) or alkynyls (IX) and (XI) follows Diels‐Alder methodology.